2001
DOI: 10.1016/s1010-7940(01)00683-2
|View full text |Cite
|
Sign up to set email alerts
|

Left ventricular architecture after valve replacement due to critical aortic stenosis: an approach to dis-/qualify the myth of valve prosthesis–patient mismatch?☆

Abstract: The left ventricular geometry and transprosthetic velocities resulted in the same postoperative recovery for both EXMIS and NOMIS patients. The presented data showed that valve prosthesis-patient mismatch had no influence in several stepwise logistic regression models. We conclude that modern mechanical bileaflet prostheses allow both acceptable hemodynamics and recovery of left ventricular hypertrophy, even in small aortic annuli.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
26
0

Year Published

2005
2005
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(30 citation statements)
references
References 16 publications
4
26
0
Order By: Relevance
“…The Doppler gradients across the present standard St. Jude bileaflet disc valves showed the same dependency of valve size as in a multitude of other studies. The present gradients measured at 10 years seemed to be consistently lower than gradients of the standard St. Jude valve (4) and the Carbomedics valve (16,17) measured within 2 years after AVR, and similar to or slightly higher than the gradients of size improved bileaflet disc valves (4,18,19). A significant increase in peak gradient from 1.5 years to 10 years after AVR in the present study was only observed in the few patients with the risk factors (unchanged supranormal LVEF, severe size mismatch, or normal LVEF hypertension) that identified peak gradients above 35 mmHg at 10 years.…”
Section: Discussionsupporting
confidence: 51%
“…The Doppler gradients across the present standard St. Jude bileaflet disc valves showed the same dependency of valve size as in a multitude of other studies. The present gradients measured at 10 years seemed to be consistently lower than gradients of the standard St. Jude valve (4) and the Carbomedics valve (16,17) measured within 2 years after AVR, and similar to or slightly higher than the gradients of size improved bileaflet disc valves (4,18,19). A significant increase in peak gradient from 1.5 years to 10 years after AVR in the present study was only observed in the few patients with the risk factors (unchanged supranormal LVEF, severe size mismatch, or normal LVEF hypertension) that identified peak gradients above 35 mmHg at 10 years.…”
Section: Discussionsupporting
confidence: 51%
“…16,28 Most studies using the indexed GOA have failed to find any significant relation between this parameter and adverse clinical outcomes. 10,11,13,28,29 This should, however, come as no surprise because, as mentioned, the indexed GOA does not bear any relationship whatsoever to postoperative hemodynamics. In contrast, the indexed EOA has consistently been shown to correlate with postoperative gradients as well as being highly predictive of adverse outcomes.…”
Section: Definition Of Ppmmentioning
confidence: 93%
“…Some authors have indeed attempted to characterize PPM using the internal geometric orifice area (GOA) of the prosthesis rather than the EOA because it is more reproducible. 10,11,13,28,29 The GOA is a static manufacturing specification based on the ex vivo measurement of the diameter of the prosthesis. The criteria used for its measurement unfortunately differ from one type of prosthesis to the other so that, for instance, the IGA grossly overestimates the EOA but to a much larger extent in the case of a bioprosthesis than in the case of a mechanical prosthesis (Figure 3).…”
Section: Definition Of Ppmmentioning
confidence: 99%
“…As well, most studies that have used the indexed IGA have failed to find any significant relation between this parameter and adverse Abbreviations: AVR, aortic valve replacement; BSA, body surface area; CFR, coronary flow reserve; EOA, effective orifice area; IGA, internal geometric area; LV, left ventricular; PPM, prosthesis-patient mismatch; TPG, transvalvar pressure gradient clinical outcomes (table 2). [21][22][23][24][25] This should, however, come as no surprise since, as mentioned, the indexed IGA does not bear any relation whatsoever to postoperative haemodynamic function. 14 19-21 In contrast, the indexed EOA has consistently been shown to correlate with postoperative gradients (fig 1, fig 3B), as well as being highly predictive of adverse outcomes (table 2).…”
Section: Parameter Used To Define Mismatchmentioning
confidence: 99%